Uplifting communities through digital literacy in the Malaysian context the story of UMP STEM LAB - Nurul Hazlina, Noordin (2020)
The education transformation generally begins with DIGITISATION in education, involving the way how knowledge is taught and preserved. Today, more than ever, the learning materials are converted into digital formats. The larger the amount of information is available through digital learning using various technical tools, the greater number of data can be displayed, and numerous creative animated learning materials covering theoretical knowledge such as science and engineering concepts are presented more interestingly and interactively.